Biological properties of the compounds formed by the combination of the 1,2,4-triazoles, furans and other functional substitutes - D. M. Danilchenko; V. V. Parchenko; O. I. Panasenko; Ye. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. To study biological properties of the compounds formed by the combination of the 1,2,4-triazoles, furans and other functional substitutes.